Justice Done: Outlawry Crimes in Medieval Iceland - Stapleton, Sarah (Marshall Digital Scholar, 2015)
Examining the Grágás and sagas of Medieval Iceland demonstrates that the laws which governed Medieval Iceland were both strict and lawbreakers were punished ruthlessly when those laws were broken. Despite this, the laws protected the injured party and the families, dependents, and mortgagees of outlaws. Outlawry crimes were broken into main categories: honor crimes, violent crimes, and crimes of wealth. By examining the Grágás and sagas one can see how the laws manifested themselves in Icelandic society.